The Costs and Benefits of Rules of Origin in Modern Free Trade Agreements - Emanuel Ornelas; John L. Turner (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the welfare impact of rules of origin in free trade agreements where final-good producers source customized inputs from suppliers within the trading bloc. We employ a property-rights framework that features hold-up problems in suppliers' decisions to invest, and where underinvestment is more severe for higher productivity firms. A rule of origin offers preferred market access for final goods if a sufficiently high fraction of inputs used in the production process is sourced within the trading bloc. Such a rule alters behavior for only a subset of suppliers, as some (very-high-productivity) suppliers comply with the rule in an unconstrained way and some (very-low-productivity) suppliers choose not to comply. For those suppliers it does affect, the rule increases investment, but it also induces excessive sourcing (for given investment) within the trading bloc. From a social standpoint, it is best to have a rule that affects high-productivity suppliers. The reason is that the marginal net welfare gain from tightening the rule increases with productivity. Therefore, when industry productivity is high, a strict rule of origin is socially desirable; in contrast, when industry productivity is low, no rule of origin is likely to help. Regardless of the case, a sufficiently strict rule can (weakly) ensure welfare gains.
Keywords: F13; F15; L22; D23; 330; hold-up problem; sourcing; incomplete contracts; regionalism